2008
DOI: 10.1159/000109390
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent for Gastrointestinal Endoscopy: A View of Endoscopists in Croatia

Abstract: Background/Aim: There are many differences and deficiencies in the process of informed consent. The aim of this study was to get the view of gastrointestinal endoscopists in Croatia on obtaining patients’ consent before endoscopic procedures. Methods: During the 2004 annual meeting of the Croatian Society of Gastroenterology, endoscopists were asked to answer a questionnaire according to common clinical practice in affiliated institutions. It included questions on endoscopists’ experience and education in medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In Croatia, there are no general recommendations determining which procedures require the patient's written consent and there is no systematic training in this field (14). The law also does not define a common form for consent, but mandates individual health care institutions to develop their own forms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Croatia, there are no general recommendations determining which procedures require the patient's written consent and there is no systematic training in this field (14). The law also does not define a common form for consent, but mandates individual health care institutions to develop their own forms.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians' knowledge and attitudes toward informed consent considerably differ in various countries and among different medical specialists (14)(15)(16)(17). We conducted this study to compare knowledge and practices for obtaining informed consent for medical procedures between 3 groups of specialists.…”
mentioning
confidence: 99%
“…20 Even after the implementation of the Act on the Protection of Patients' Rights, Bani ć et al found that 35 percent of patients going for gastroenterology endoscopy gave only verbal consent, and 12 percent of patients did not give either written or verbal consent. 21 In 17 percent of cases, the information was given to patients by nurses (who typically have only a middle-school or higher education level), not by physicians, as is required by the Croatian Act on the Protection of Patients' Rights. According to the law, only persons with a college degree working in the healthcare system can obtain valid informed consents.…”
Section: Informed Consentmentioning
confidence: 99%